2015
DOI: 10.1016/j.neurobiolaging.2014.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Cortical pyroglutamate amyloid-β levels and cognitive decline in Alzheimer's disease

Abstract: Posterior cingulate cortex (PCC) accumulates amyloid-β (Aβ) early in Alzheimer’s disease (AD). The relative concentrations of full-length Aβ and truncated, pyroglutamate-modified Aβ (NpE3) forms, and their correlations to cognitive dysfunction in AD, are unknown. We quantified AβNpE3-42, AβNpE3-40, Aβ1−42, and Aβ1-40 concentrations in soluble (nonfibrillar) and insoluble (fibrillar) pools in PCC from subjects with an antemortem clinical diagnosis of no cognitive impairment, mild cognitive impairment, or mild-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Moreover, 5-OP should be of interest to neurochemists as a result of recent findings relating to Alzheimer disease (AD). A portion of Aβ peptide—a contributor to amyloid formation in the brain and a probable neurotoxin contributing to AD pathology—has recently been found to be truncated and to contain an N terminal 5-OP [ 32 , 33 ]. The full-length Aβ and the truncated forms have been designated fl-Aβ and pGlu-Aβ(3-40/42), respectively [ 32 ].…”
Section: Glutamate Formation In the Brain—important Roles Of Glutamentioning
confidence: 99%
“…Moreover, 5-OP should be of interest to neurochemists as a result of recent findings relating to Alzheimer disease (AD). A portion of Aβ peptide—a contributor to amyloid formation in the brain and a probable neurotoxin contributing to AD pathology—has recently been found to be truncated and to contain an N terminal 5-OP [ 32 , 33 ]. The full-length Aβ and the truncated forms have been designated fl-Aβ and pGlu-Aβ(3-40/42), respectively [ 32 ].…”
Section: Glutamate Formation In the Brain—important Roles Of Glutamentioning
confidence: 99%
“…Also, it has been demonstrated that pGlu-3 Aβ may act as a nidus for template-induced protein misfolding and oligomerization, both with itself and with free Aβ1-42 to generate cytotoxic low-molecular weight oligomers (Nussbaum et al, 2012). Recently, QC expression and pGlu-3 Aβ accumulation in human AD brain has been shown to correlate with cognitive decline (Morawski et al, 2014, Pivtoraiko et al, 2014) and tau pathology (Mandler et al, 2014). Thus, cumulating evidence from human post-mortem tissue and mouse models suggest pGlu-modified Aβ as a species causally involved in AD progression and cognitive decline (Rijal Upadhaya et al, 2014, Saido et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The PCC is one of the key hubs of the default mode networks and represents early densely amyloid-affected regions whether in patients with AD (Li et al, 2008 ) or in cognitively normal subjects with a positive family history of AD (Mosconi et al, 2010 ). In postmortem study, the concentration of amyloid β (A β) in the PCC GM strongly correlated with episodic memory impairment (Pivtoraiko et al, 2015 ). The PCC is known for its role of modulating information that arrives FG through the interregional connection (Vogt et al, 2006 ), and it is implicated in facial expression processing.…”
Section: Discussionmentioning
confidence: 99%